PENGEMBANGAN PENGELOLAAN KELAS DALAM MENINGKATKAN EFISIENSI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Zainuddin, Moh Riza (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
The decentralized system of education in this era give a chance to each school institutions to improve the quality of schools that participate in improving the quality of education responded by seeking to every teacher to be creative to improve classroom management appropriately for learning run efficiently and effectively. Arguing that the media class is meeting all the educational component as well as the cutting edge and also educational base. This class management concept seeks to provide a solution to the problem in the class, whose scope is not limited to delivery of content, but also includes some things thoroughly to organize classes include: first academic activities such as planning, implementation and assessment of learning. Both administrative activities that include activities such as procedural and organizational arrangement of the room, grouping students in the division of tasks, classroom discipline, the procurement of test, organizing classes, reporting. So the concept of classroom management is trying to empower the potential of existing classes as optimally as possible to support the process of educational interaction in achieving learning goals that are particularly effective in the material Islamic Education.Sistem desentralisasi pendidikan di era sekarang ini memberikan peluang kepada setiap lembaga sekolah untuk meningkatkan kualitas mutu sekolah yaitu ikut merespon dalam meningkatkan mutu pendidikan dengan mengupayakan kepada setiap guru untuk berkreasi meningkatkan pengelolaan kelas dengan tepat agar pembelajaran berjalan secara efisien dan efektif. Dengan alasan bahwa kelas merupakan media pertemuan segala komponen pendidikan serta ujung tombak dan juga basis pendidikan. Konsep pengelolaan Kelas ini berusaha untuk memberikan penyelesaian terhadap masalah di kelas, yang cakupannya tidak hanya terbatas pada penyampaian materi saja, akan tetapi mencakup beberapa hal yang menyeluruh untuk mengorganisasi kelas antara lain: pertama kegiatan akademik berupa perencanaan, pelaksanaan dan penilaian pembelajaran. Kedua kegiatan administratif yang mencakup kegiatan procedural dan organisasional seperti penataan ruangan, pengelompokan siswa dalam pembagian tugas, penegakan disiplin kelas, pengadaan tes, pengorganisasian kelas, pelaporan. Jadi konsep pengelolaan kelas adalah berusaha memberdayakan potensi kelas yang ada seoptimal mungkin untuk mendukung proses interaksi edukatif dalam mencapai tujuan pembelajaran yang efektif khususnya dalam materi Pendidikan Agama Islam.